If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x+3(2x-4)=3(x-6)
We move all terms to the left:
8x+3(2x-4)-(3(x-6))=0
We multiply parentheses
8x+6x-(3(x-6))-12=0
We calculate terms in parentheses: -(3(x-6)), so:We add all the numbers together, and all the variables
3(x-6)
We multiply parentheses
3x-18
Back to the equation:
-(3x-18)
14x-(3x-18)-12=0
We get rid of parentheses
14x-3x+18-12=0
We add all the numbers together, and all the variables
11x+6=0
We move all terms containing x to the left, all other terms to the right
11x=-6
x=-6/11
x=-6/11
| 7=p+10 | | 6/b=8/3 | | -3n-21=-18 | | 6.6x+9.8=16.1x+9.8 | | 6(1-8r)=-7r+6 | | J(×)=2x+9 | | .14=3x-2 | | 5x-6+x+2=-5x+6-15 | | 2w^2+21w+10=0 | | 8(6x+10)=-8 | | 65=9x+6 | | 17x+14+4x=-2 | | m-10=28 | | 3(y+8)=4(y-4 | | 3p^2-47p-16=0 | | 14x=x-17 | | 4(2x+8)=-13+29 | | -3/8h=6 | | -123=3-6(2k+5 | | -17+7x=31+10x | | 228=19r | | 6x-13=4x+2x | | 24+3x9x=x | | p=1=-4 | | (9x+3)+114=180 | | –9s+7=7−9s | | 5d-12-d+9d=53=d | | (b-7/6)=2 | | k^{2}+5k-16=0 | | x-(-12)=-13 | | 13s^2-14s+1=0 | | 64=x2÷4 |